THE CONCEPT OF EXISTENTIALISM, ITS CHARACTERISTICS - Yuldashev Farrux Abduraxmanovich (Web of Journals Publishing, 2025)
This article analyzes the socio-philosophical views on Existence: the idea that a person remains at his own discretion, that only he decides what to do and is responsible for his actions, and that each person's existence is unique.
Keywords: Person, existence, worldview, development, society, independent thought, freedom of will, self-awareness, existential approaches.